"Drunkorexia": Understanding eating and physical activity behaviors of weight conscious drinkers in a sample of college students. Issue 7 (3rd October 2017) - Wilkerson, Amanda H.; Hackman, Christine L.; Rush, Sarah E.; Usdan, Stuart L.; Smith, Corinne S.
ABSTRACT: Objective : Behaviors of weight conscious drinkers (BWCD) include disordered eating, excessive physical activity (PA), and heavy episodic drinking. Considering that approximately 25% of the college students report BWCD, it is important to investigate what characteristics increase the likelihood of college students engaged in BWCD for both moderate and vigorous PAs.Participants : A total of 510 college students were recruited from a large, public southeastern university.Methods : Participants completed a cross-sectional survey during the spring 2015 semester.Results : Of 510 respondents, 11.2% reported moderate PA-based BWCD and 14.7% reported vigorous PA-based BWCD. Weight loss intention, BMI and Greek affiliation predicted both moderate and vigorous BWCD.Conclusions : Study findings suggest that Greek-affiliated students and students with weight loss intentions might be at an increased risk for BWCD. Along with promoting lower levels of alcohol consumption, college practitioners should consider discussing issues of weight and body image with college students as they relate to maladaptive drinking behavior.